Broadband acoustic signal enhancement via gradient metamaterials coupled to crystals - Zhang, Sai; Hao, Guodong; Zhao, Xinsa; Liu, Yexin; Han, Jianning (Frontiers in Physics, 2023)
In this work, a phononic crystal gradient metamaterial structure (PCGMs) is proposed based on the strong wave compression effect coupled with equivalent medium theory to achieve enhancement and directional sensing of weak target acoustic signals. Compared with the conventional gradient structure, PCGMs exhibit superior acoustic enhancement performance and wider range of acoustic response capability. Numerical analysis and experimental validation consistently demonstrate that PCGMs can effectively enhance the target frequency signals in harmonic signals. This study breaks through the detection limit of acoustic sensing systems and provides a great method for engineering applications of weak acoustic signal perception.